First report of the enset root mealybug Paraputo ensete (Williams & Matile Ferrero) (Hem.: Pseudococcidae) on banana in Ethiopia - Erenso, Fikadu; Blomme, Guy; Goergen, Georg E.; Muanenda, Mitiku; Kearsley, Elizabeth; Addis, Temesgen (Springer, 2023)
Enset root mealybugs, a major pest affecting the cultivation of the enset crop in the Ethiopian highlands, have for the first time been observed on banana mats indicating the potential host status of Musa spp. These observations were made under natural conditions in backyard gardens in the Gedeo zone, southern Ethiopia, on the root system of banana mats of the ‘Pisang Awak’ (local name ‘Feranji Muz’, ABB genome group) landrace. Here, we confirm the identification of the collected enset root mealybug specimens on banana mat root systems as Paraputo ensete (Williams & Matile-Ferrero) (Hemiptera: Pseudococcidae) through DNA analysis.